How learning technologies are transforming studies at IIUM? - Ahmad H.Osman, Rahmah (2018)
Education transformation is not about “googlization of everything”. In view of the technological and innovative avalanche in Education worldwide, which has spilled over into the Malaysian educational ecosystem, i.e., the 10 shifts prescribed in the Malaysian Education Blueprint, IIUM has embraced the IOT and technologies in our Teaching and Learning environment. However, as the Garden of Knowledge and Virtue, the academics are continuously reminded about The National Philosophy in Education, The “Falsafah Pendidikan Negara”. The “Falsafah Pendidikan Negara” is designed to produce Malaysian citizens who are knowledgeable and competent, who possess high moral standards, and who are responsible and capable of achieving a high level of personal wellbeing as well as being able to contribute to the harmony and betterment of the family, society and nation at large.